A strong zero-phonon line red phosphor BaNbF7:Mn4+ for white LEDs. Issue 18 (5th August 2020) - Zhou, Yang; Wang, Xiaoming; Wang, Cuiping; Zhang, Tian; Wang, Yonggang; Dou, Fan; Jiao, Huan
Abstract : A novel red fluoride phosphor BaNbF7 :Mn 4+ was synthesized by co-precipitation method. Under UV and blue light excitation, this phosphor shows strong ZPL emission intensity at 630 nm and which makes it an attractive red phosphor candidate for WLEDs. Abstract : A novel red fluoride phosphor BaNbF7 :Mn 4+ was synthesized via the conventional co-precipitation method. The structure and luminescence properties of BaNbF7 :Mn 4+ were investigated and discussed under various conditions. The BaNbF7 :Mn 4+ phosphor shows strong ZPL emission intensity at about 630 nm under ultraviolet (UV) and blue light excitation. It originated from the highly distorted Mn 4+ octahedral coordination environment in the C 3v group symmetry surrounding. A WLED fabricated with a blend of YAG:Ce 3+ and the BaNbF7 :Mn 4+ phosphor exhibits a low color temperature (CCT = 3715 K) and a high color rendering index ( R a = 81.2), indicating its potential for application as a red phosphor for WLEDs.